Modes of governance for market entry by international franchisors: factors affecting the choice. Issue 6 (21st December 2020) - Hoffman, Richard; Watson, Sharon; Kher, Hemant
Abstract : Purpose: This study aims to provide an empirical test of an existing theoretical model depicting the governance modes used by international franchisors when entering international markets. Design/methodology/approach: Using a unique panel data set of 222 market expansions by US firms over a seven-year period, this paper tests hypotheses regarding the factors affecting the franchisors' choice of governance modes when entering foreign markets. Findings: Franchisors use governance modes with lower levels of control when faced with environmental uncertainties due to corruption, economic downturns and when the geographic distance is large. Moreover, the franchise system assets and its local market assets also affect the choice of governance modes. Practical implications: Firms need to balance the costs of environmental uncertainty with the need to safeguard the firm's capabilities and resources using governance modes with appropriate levels of control. This balance changes as the franchise company gains more experience in the local market and as once-emerging markets continue to develop. Originality/value: This research identified additional governance modes used by franchisors compared to previous studies. Using multiple theoretical perspectives, the study supported significant portions of the Jell-Ojobor and Windsperger (2014) model of franchisor governance mode choice.